Cystic Fibrosis Heterogeneity and Personalized Treatment - Wat, Dennis; Nazareth, Dilip (IntechOpen, 2020)
Cystic Fibrosis - Heterogeneity and Personalized Treatment provides the latest research and clinical evidence for clinicians, scientists and researchers involved in the care of patients with cystic fibrosis (CF). This book outlines the burden of the CF microbiome, utilisation of CF registries to impact future care, the sequelae of hepatobiliary complication, the use of upcoming technologies to provide patient-centred care, and provides an overview of cystic fibrosis transmembrane regulator (CFTR) modulators. Looking after patients with CF is highly rewarding, allowing those of us to combine our dedication and problem-solving skills to create a personalized approach. This book is invaluable for those involved in the care of CF patients.